Molecular detection, not extended culture incubation, contributes to diagnosis of fungal infection - Alex Zhu (BMC, 2021)
Abstract Background Despite its low sensitivity, fungal culture remains one of the key methods for diagnosis and treatment of fungal infections, as it identifies the etiology at the genus and species level and affords the opportunity for susceptibility testing. The Manual of Clinical Microbiology recommends that fungal culture screening for all pathogens should routinely be held for 4 weeks to maximize the recovery of slow-growing species. Information on the optimal fungal culture time in this era of expansion of immunocompromised populations and availability of molecular diagnostics is lacking. We reviewed our experience with fungal culture to determine the optimal culture incubation time. In addition, our experience of broad-range ITS PCR for diagnosis of culture-negative fungal infections was also reviewed. Methods Fungal culture and ITS PCR results from January 1, 2013, to December 31, 2017, were reviewed. Results This study included 4234 non-duplicated positive cultures. Ninety-six percent (4058) of the positive cultures were detected in the first 7 days of incubation. During the second week of incubation, 111 (2.8%) positives were detected from day 8 to day 10, and 71 (1.7%) were detected from day 11 to day 14. Only 6 (0.1%) positive cultures were detected in the third week of incubation, and no positive culture was detected in the fourth week of incubation. No clinically significant fungal isolates were recovered after 14 days. Clinically significant pathogens were detected in 16 (0.2%) culture-negative samples by ITS PCR. Conclusion Extending culture incubation beyond 2 weeks did not generate clinically relevant results. When culture failed to make a laboratory diagnosis, broad-range internal transcribed spacer (ITS) rRNA gene PCR followed by sequencing produced clinically significant results.